Peningkatan kemampuan pemecahan masalah daur air melalui model problem based learning (pbl) pada peserta didik kelas v sekolah dasar - Hanitia Putri Ramadhani; Sandra Bayu Kurniawan; Sularmi Sularmi (Didaktika Dwija Indria, 2019)
The purpose of this research is improving the ability to solve water cycle problems  by applying problem based learning model. This research is Classroom Action Research with two cycles. The subjects of this research were students of the 5th students at SD Negeri Munggung I Surakarta in the 2018/2019 academic year, totalling 19 students. This research uses data collection techniques in the form of interview, observation, field notes, tests, and documentation with data analysis of content validity and triangulation. The analysis of the data used is the interactive analysis model of Miles-Huberman. The first cycle resulting in a percentage of 52.63% in classical, and the study continued with the second cycle with the percentage of 84.21% in classical terms. Based on the result of the research, it can be conclude that the ability to solve water cycle problems on 5th students of SD Negeri Munggung I Surakarta in the 2018/2019 academic year can be improved through the Problem Based Learning model.